Safe food preparation with natural eclipta alba leaf antimicrobial polyphenol : A preventin strategies for leptospira infection during and after a flood. - Sreenivasan, Sasidharan (Universiti Sains Malaysia, 2016)
Leptospirosis is an infection caused by corkscrew-shaped bacteria called Leptospira interrogans. number of leptospirosis cases normally increased following massive floods via the ingestion of contamin dirty floodwater as the primary source of the organism. Therefore, the current study was undertake evaluate the in vitro antimicrobial activity of Eclipta alba L. polyphenol against L. interrogans and to eval the application of this natural polyphenol in the cooked rice and tea for safe food preparation to prevent the interrogans infection.